Humor in School Jokes: A Pragmatic Study - Gabriella Novianty Soedjarmo; Prabarini Dwi Pangestu; Ni Nyoman Wartinah (Indonesian Journal of English Language Studies (IJELS), 2016)
In our lives, there are many instances where we encounter jokes. The media; printed, online, or broadcasted, presents jokes in many ways. Some television programs have their own form of humour such as through talk shows or other kinds of performances. In printed media, we can read humour through comic. Online media also provides certain sites to deliver jokes. We are familiar with 9gag or other sites which post funny pictures or memes. This paper is going to analyse how the jokes in online media is presented using a pragmatic point of view. The researchers took the data from the website and chose the joke about school life and analysed the 30 school jokes using the reference and maxim theory. The result of this study shows that in order to create a school joke, the joke maker violates the reference and maxim.